Postoperative myocardial injury and platelet reactivity in patients undergoing vascular surgery: The platelet reactivity and postoperative myocardial injury after major vascular surgery (PROMISE) study. Issue 218 (October 2022) - Zheng, K.L.; Bor, W.L.; Vernooij, L.M.; Breet, N.C.; Kelder, J.C.; Hackeng, C.M.; Kropman, R.H.J.; ten Berg, J.M.; Noordzij, P.G.
Abstract: Background: Postoperative myocardial injury (PMI) after major vascular surgery, detected by elevated cardiac troponin (cTn), has been associated with morbidity and mortality. It is unclear whether the pathophysiology of PMI is determined by increased platelet activity. Objective: To examine the relationship between platelet activation (P-selectin expression) and PMI in patients undergoing elective open abdominal aortic surgery. Methods: This prospective, single-centre, observational, cohort study included 33 patients undergoing elective open abdominal aortic surgery between March 2018 and April 2021. Patients were routinely treated with aspirin. Unstimulated platelet activation was measured by platelet bound P-selectin expression (range 0–100 %). Explorative coagulation measurements were: stimulated platelet aggregation measured with the VerifyNow® assay (aspirin cartridge), with the Multiplate® analyzer (ASPI, ADP and TRAP) and stimulated coagulation status evaluated by the TEG® Hemostasis Analyzer System (global hemostasis cartridge). The primary outcome was cTn release assessed by the fifth generation high-sensitive cTn assay. Multivariable generalized linear mixed models were used to evaluate the association between platelet function and cTn concentrations over time. Results: Ten patients (30.3 %) developed PMI. Increased P-selectin expression directly after surgery was associated with the cTn concentrations over 48 h (β = 1.39 (1.1–1.75), P  = 0.0064). No association was found between P-selectin measured later after surgery (at 24 h or 48 h) and cTn concentrations. Furthermore, there was no association between the explorative coagulation parameters and cTn release. Conclusion: Platelet reactivity, assessed by P-selectin expression measured directly after surgery is associated with PMI, assessed by elevated cTn concentrations in the early postoperative period in patients undergoing elective open abdominal aortic surgery.